The speckled band - Evans, Virginia (Illustrated readers)
Two years ago her sister, Julia, died in mysterious circumstances. Now Helen is terrified that her life is in danger. Can the brilliant detective, Sherlock Holmes, solve Julia´s murder and save Helen?